2020
DOI: 10.1111/1750-3841.15468
|View full text |Cite
|
Sign up to set email alerts
|

Antibrowning effect of commercial and acid‐heat coagulated whey on potatoes during refrigerated storage

Abstract: Potato color turns to brown after some process such as peeling, cutting, and slicing. In this research, the effect of acid‐heat coagulated whey and commercial whey solutions on the color, polyphenol oxidase, phenylalanine ammonia‐lyase activity, malondialdehyde, hydrogen peroxide content of potatoes were compared with pure water (control) immersion and sodium hydrogen sulfide solution. According to color results, there was no significant (P > 0.05) difference was found in the L* and b* values, browning index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The total flavonoid content (quercetin) of mung bean seed coat heated at 120 • C for 20-50 min increased from 2.93 ± 0.51 to 18.74 ± 0.41 (µg/mg); thus, the content was statistically significantly different from the heat processing time (Figure 3a) (p < 0.05). However, flavonoids are chemically reactive and easily oxidized to quinones; quinones can be condensed with other polyphenolic compounds to form dark-brown polymers [50]. The condensation of flavonoids to form a dark-brown mass may be closely related to the reduced L-value obtained in this study by thermal treatment of seed coats.…”
Section: Flavonoid Condensation Reactionmentioning
confidence: 61%
“…The total flavonoid content (quercetin) of mung bean seed coat heated at 120 • C for 20-50 min increased from 2.93 ± 0.51 to 18.74 ± 0.41 (µg/mg); thus, the content was statistically significantly different from the heat processing time (Figure 3a) (p < 0.05). However, flavonoids are chemically reactive and easily oxidized to quinones; quinones can be condensed with other polyphenolic compounds to form dark-brown polymers [50]. The condensation of flavonoids to form a dark-brown mass may be closely related to the reduced L-value obtained in this study by thermal treatment of seed coats.…”
Section: Flavonoid Condensation Reactionmentioning
confidence: 61%
“…The amount of water-soluble protein in YS was found to be 0.96 g/L. Proteins have antioxidant properties because they can eradicate free radicals and neutralize reactive oxygen species, and their thiol group content delays enzymatic browning. , It has been reported that immersion of cut potatoes in whey protein solution inhibits PPO activity up to the third day of storage . Titration acidity of YS was found to have 1.25% lactic acid equivalent.…”
Section: Resultsmentioning
confidence: 94%
“…20,25 It has been reported that immersion of cut potatoes in whey protein solution inhibits PPO activity up to the third day of storage. 19 Titration acidity of YS was found to have 1.25% lactic acid equivalent. In a study, it was reported that 1% lactic acid moderately prevented the browning of apple slices.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations